05 The electro-mechanical window as Torsade de Pointes risk marker in conscious and anaesthetised dogs after IKS blockade. Issue 1 (10th December 2010) - van der Linde, H J; Cools, F; Vanlommel, A; Janssens, S; Verrelst, J; Van Deuren, B; Somers, Y; Teisman, A; Towart, R; Gallacher, D J
Abstract : The electro-mechanical window (EMw) is a recently proposed biomarker describing the temporal difference between electrical and mechanical events in beating hearts and is a precursor to identify Torsade de Pointes (TdP) risk in the anaesthetised dog.1 In follow-up studies, conscious dogs (n=6; telemetered) showed comparable baseline values to anaesthetised dogs (n=20): QT=250 vs 252 ms, QLVPend=347 vs 339 ms and EMw=+96 vs +87 ms, respectively. To compare the EMw in conscious and anaesthetised dogs after IKs blockade.2 Six conscious dogs were orally treated with JNJ303 (20 mg/kg) and four anaesthetised dogs received infusions of JNJ303 (cumulative 2.5 mg/kg). In both conditions JNJ303 induced QT prolongation, a large negative EMw and TdP appeared in 50% of the dogs in each condition (pause-dependent and adrenergic-dependent). In the conscious dogs significant differences in maximum plasma levels (PL), QT and EMw were observed between dogs that induced TdP and those without TdP: PL (4950 vs 1473 ng/ml), QT (427 vs 351 ms) and EMw (−150 vs −68 ms), without differences in RR (642 vs 654 ms) and QLVPend (273 vs 287 ms), respectively. Also in anaesthetised dogs long QT (766 ms) and large negative EMw (−445 ms) at similar PL (5743 ng/ml) were observed. In conclusion a potent IKs blocker (JNJ303) can cause TdP in conscious and anaesthetised dogs, coupled with a large negative EMw.